Citra Perusahaan Asuransi Kredit Modal Kerja di Jawa Barat - Amron, Amron Amron (MEDIA EKONOMI & TEKNOLOGI INFORMASI, 2013)
This research is aimed to analyze and to know influence significan of performance promotion program decision to working capital credit insurance company image in West Java, Indonesia.